Poly(A) Signals Located near the 5' End of Genes Are Silenced by a General Mechanism That Prevents Premature 3'-End Processing. - Guo, J.; Garrett, M.; Micklem, G.; Brogna, S. (Molecular and Cellular Biology, 2011)
Poly(A) signals located at the 3' end of eukaryotic genes drive cleavage and polyadenylation at the same end of pre-mRNA. Although these sequences are expected only at the 3' end of genes, we found that strong poly(A) signals are also predicted within the 5' untranslated regions (UTRs) of many Drosophila melanogaster mRNAs. Most of these 5' poly(A) signals have little influence on the processing of the endogenous transcripts, but they are very active when placed at the 3' end of reporter genes. In investigating these unexpected observations, we discovered that both these novel poly(A) signals and standard poly(A) signals become functionally silent when they are positioned close to transcription start sites in either Drosophila or human cells. This indicates that the stage when the poly(A) signal emerges from the polymerase II (Pol II) transcription complex determines whether a putative poly(A) signal is recognized as functional. The data suggest that this mechanism, which probably prevents cryptic poly(A) signals from causing premature transcription termination, depends on low Ser2 phosphorylation of the C-terminal domain of Pol II and inefficient recruitment of processing factors.